Questioning a Previous Autism Spectrum Disorder Diagnosis: Can You "Lose" the Diagnosis?. Issue 4 (May 2020) - Zaro, Christopher; Jeon, Hyejin; Harstad, Elizabeth; Conrad, Cassandra; Solomon, Dasha; Augustyn, Marilyn
Abstract : CASE: Heidi is an almost 6-year-old girl presenting to your primary care office to establish care because of a change in insurance status. You review her previous medical records before seeing her. She was diagnosed with autism spectrum disorder (ASD) when she was 25 months old. Her parents were initially concerned about language delay. Through a comprehensive evaluation by a developmental-behavioral pediatrician and a child psychologist, including administration of the Bayley Scales of Infant and Toddler Development and the Autism Diagnostic Observation Schedule, she was diagnosed with ASD. Her cognitive skills were reported to be within the average range. Soon after the diagnosis, she began receiving 20 hours of applied behavioral analysis (ABA) per week, as well as music therapy, occupational therapy, and a toddler playgroup through early intervention. Four months after the initial diagnosis, her parents reported that she had started making small improvements in her behavior, used more eye contact, and seemed more socially engaged. Approximately 1 year after the diagnosis, she was receiving 6 hours of ABA per week in addition to starting preschool with an Individualized Education Program. She reportedly continued to show progress with social communication and pretend play skills. At the age of 3 years, 8 months, neuropsychological testing was completed at her parent's request, and her cognitive skills and adaptive skills were reported to be within the average range. She continued to meet the diagnostic criteria for ASD, given her challenges with social awareness, communication, delayed play skills, decreased flexibility, and tendency toward subtle self-direction. She continued to receive speech/language therapy and attended an integrated preschool program within the school district because of her social and communication challenges. She also received ABA 4 hours weekly at home. During your first visit with Heidi, her parents report that she has continued to make progress in all areas, including social skills. She can engage in imaginary play with her friends, ask strangers questions, and comprehend the perspective of others, and she is no longer "rigid." She is not receiving services outside of school and is only receiving once weekly speech/language therapy in school. Her parents no longer believe that she meets the criteria for ASD, and they are interested in further evaluation. Her parents ask if it is possible to "lose" the diagnosis of ASD. They also want to know if there are other things to be concerned about for her future. How do you respond?